A Study on the Motivations and Challenges in the Adoption of Virtual Agents in the Services Sector - Jayakumar, Venkatesh Nambakkam (Digital Repository of Theses - SSBM Geneva, 2024)
This expanded analysis delves into the dynamics of integrating virtual agents within the services sector, focusing on understanding industry adoption through the lens of two theoretical frameworks: the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Technology Threat Avoidance Model (TTAT). By examining responses from 628 participants, this study highlights the dual role of perceived threats as obstacles and the positive influence of effort expectancy and social norms as facilitators in the adoption process. The research underlines the importance of these factors in shaping individual attitudes and behaviours towards virtual agents. It emphasizes that addressing concerns about threats, improving the ease of use, and capitalizing on social influences can significantly enhance the adoption rates of virtual agents. Recommendations stress the necessity of refining the user experience, fortifying security measures, and strategically employing social influence to cultivate an environment more conducive to the integration of virtual agents in service-oriented sectors. This comprehensive approach aims to offer actionable insights for stakeholders looking to navigate the complexities of technology adoption and optimize the deployment of virtual agents in their operations. Keywords: Virtual Agents, Chatbots, AI, UTAUT.